Case Method Learning Model with Cooperative Learning Approach to Improve Social Skills - Anderson, Irzal; Wahyuni, Anny; Saputra, Muhammad Adi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to improve students' social skills and learning outcomes through the case method model with a cooperative learning approach. Students ' social skills are still low, considering the indicators of group work, group presentations, discussions, and opinions that have an impact on learning outcomes. Student learning outcomes also include affective, cognitive, and psychomotor domains. This study uses a class action research method with three cycles. Each cycle consists of planning, implementation of actions, observation, analysis, and reflection. This research was carried out in Class A with a total of 32 students who are in the class of 2022 History Education Study Program, PIPS Department, FKIP, University of Jambi. Data collection techniques using observation, interviews, and literature analysis. The results showed that the application of CSE method model with a cooperative learning approach can improve students ' social skills. The percentage of social skills in the first cycle was 41.4. In the second cycle, social skills increased to 63.2, and in the third cycle, to 82.2. For the learning outcomes in the cycle, I got a score of 71.1. Cycle two increased by a value of 74.4, and cycle III got a score of 78.9. it can be concluded that the case method learning model with a cooperative learning approach to improve students' social skills.